Obasanjo, Nigeria and the world John Iliffe - Iliffe, John (James Currey, 2011)
This first full account of Obasanjo's life from 1937 to 2010 combines an analysis of an exceptionally vital and complicated man with a history of an exceptionally vital and complicated country.